KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI SISWA DI SMP AR-ROHMAH BOARDING SCHOOL DAU KABUPATEN MALANG - Pujiharti, Endang (Program Studi Manajemen Pendidikan Islam (MPI) STAI Nahdlatul Ulama (STAINU) Malang, 2022)
One of the competencies that must be possessed by the principal in carrying out his role in schools is managerial competence. This study aims to determine: 1) how the principal's leadership is to improve student achievement, 2) how the principal motivates students to improve achievement, and 3) how the principal's managerial ability is to improve student achievement at Ar Rohmah Boarding School Junior High School. This study uses a descriptive type of qualitative approach. The data collection uses interviews, documentation, and observation. Data analysis techniques include data reduction, data presentation, and concluding. The results of this study are: 1) The principal at Ar-Rohmah Boarding School Junior High School has a democratic leadership style because it always involves all school members in determining achievement targets, and is guided because he always directs that the suggestions given by school residents are rational and not deviating from the initial target, 2) Principals provide direct motivation by encouraging students to excel, as well as providing rewards for students who excel, 3) Principals apply good management to achieve student achievement targets. Every program that is run always begins with a careful planning process, followed by organizing, implementing, directing, and evaluating as a correction to all processes that have been carried out and used as a reference so that in the future it can be better.